2019
DOI: 10.1007/jhep10(2019)053
|View full text |Cite
|
Sign up to set email alerts
|

Elastic proton-proton scattering at LHC energies in holographic QCD

Abstract: The cross sections of the high energy proton-proton scattering are studied in a holographic QCD model, focusing on the Regge regime. In our model setup, the involved nonperturbative partonic dynamics is described by the Pomeron exchange, which is realized by applying the Reggeized spin-2 particle propagator together with the proton gravitational form factor obtained from the bottom-up AdS/QCD model. Our model includes three adjustable parameters which are to be fitted by experimental data. We show that both th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…It has been argued that the near-threshold photo-production of a heavy quarkonium (see [8] for an ongoing experiment) is sensitive to the gluon gravitational form factors P |T µν g |P where T µν g is the gluon part of the QCD energy momentum tensor [9][10][11] (see also [12,13]). In lepto-production at high-Q 2 , this connection can be cleanly established by using the operator product expansion (OPE) [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued that the near-threshold photo-production of a heavy quarkonium (see [8] for an ongoing experiment) is sensitive to the gluon gravitational form factors P |T µν g |P where T µν g is the gluon part of the QCD energy momentum tensor [9][10][11] (see also [12,13]). In lepto-production at high-Q 2 , this connection can be cleanly established by using the operator product expansion (OPE) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the present model, there are four parameters in total, α c (0), α c , λ π , and λ p , which need to be determined by the experimental data. However, the three of those were determined in the preceding study of the proton-proton scattering [37], and we can use the resulting values for the pion-proton and pion-pion cases by virtue of the universality of the Pomeron. In Ref.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We extend the work presented in Ref. [37], in which the elastic proton-proton scattering was studied in a holographic QCD model, and investigate the pion-proton and pionpion scattering, focusing on the Regge regime. In our model, the Pomeron is described by the Reggeized spin-2 particle propagator, and the proton-Pomeron and pion-Pomeron couplings are given by gravitational form factors of the proton and pion, which can be obtained from the bottom-up AdS/QCD models [40,41].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, QCD theory is a strong coupling theory. Gauge/gravity duality [20][21][22][23], breaking the conformal symmetry at low energy, provides a very important a email: yanqzhao@qq.com b email: zhuzhourun@mails.ccnu.edu.cn c email: chenxun@ihep.ac.cn tool to research the properties of hadron physics in a strong coupling systems [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Many scholars used holographic approach to study imaginary potential by considering various background like taking into account of chemical potential [44], they observed that the presence of the chemical potential decreases the dissociation length.…”
Section: Introductionmentioning
confidence: 99%